Financial ratios and their role in predicting stock prices A case study of companies listed on the Damascus Stock Exchange - اسماعيل, رولا (Latakia University Journal - Economic and Legal Sciences Series, 2023)
This study aimed to demonstrate the importance of financial analysis in evaluating the performance of companies, and to verify the possibility of relying on financial ratios to predict the performance of companies. The study relied on the data of the companies listed on the Damascus Stock Exchange, during the period from 2010 to 2020. The study included an econometric study of the relationship between financial ratios (liquidity ratios, share turnover rate, return on equity, total income/total assets, debt ratio) and the market value of the share. The study concluded that there is a significant relationship between each of the debt ratio, liquidity ratios and the market value of the share, while the relationship between the market value of the share and each of the share turnover rate, return on equity, and total income / total assets was not significant, and this indicates Although the company's financial ratios can give an idea of its financial performance, stability and ability to grow, it is not always a strong indicator of the market value of the company's shares. As the relationship between the financial ratios and the market value of the company's shares may be affected by other factors.